ANALISIS REKONSILIASI FISKAL DALAM MENENTUKAN PAJAK PENGHASILAN TERUTANG PT. MNO TAHUN 2020 - Michelle, Michelle; Widjaja, Purnamawati Helen (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to determine whether the recognized expenses and income in the fiscal financial statement of PT. MNO for 2020 are in accordance with the applicable tax regulations, calculate the corporate income tax for 2020, and to find out the cause of the difference between commercial financial statements and fiscal financial statements. The study applied a qualitative descriptive research design. Sample determination in this study is using probability sampling method with simple random sampling technique. The results of the study indicate that the preparation of the fiscal financial statements at PT MNO is not in accordance with the UU PPh No. 36 Tahun 2008, because there are still uncorrected expense and income accounts that affect the calculation of Corporate Income Tax Payable.